Utilização de fontes de fósforo e resíduos de leguminosas no sistema de plantio direto em solo tropical coeso - Coelho, Marta Jordana Arruda (2015)
The objective of this study was to compare the efficiency of a calcined aluminous phosphate with soluble phosphate, combined with legume residues, by determining the fate of P from these sources in a high cohesion tropical soil